Effect of Equine Chorionic Gonadotropin on Follicular and Luteal Vascularisation and Progesterone Production in Murrah Buffaloes Subjected to Ovulation Synchronisation - de Ruediger, Felipe Rydygier; de Carvalho, Nélcio Antonio T; Codognoto, Viviane M. [UNESP]; Dantas, Ariane [UNESP]; Yamada, Paulo H. [UNESP]; de Oliveira, Rogério Antônio [UNESP]; Pinheiro, João Carlos [UNESP]; Almeida Filho, Rogério A [UNESP]; Oba, Eunice [UNESP] (Wiley, 2025)
This study evaluated the effect of equine chorionic gonadotropin (eCG) on ovarian vascularisation and plasma progesterone (P4) levels in Murrah buffaloes during an ovulation synchronisation protocol. Twenty buffaloes were divided into two groups: with eCG (n = 20) and without eCG (control, n = 20) in a crossover design. A 1.0 g progesterone intravaginal device (DIB) was inserted and 2 mg oestradiol benzoate was administered intramuscularly on Day 0. On Day 9, DIB was removed, PGF2α was administered to all animals and eCG was given to half. GnRH was administered on Day 11. Daily Doppler ultrasounds assessed follicular and luteal development and vascularisation from D9 to D16 and on Days 20, 24, 28 and 32. Blood samples were collected before each ultrasound to analyse plasma P4. Ovulation occurred on Day 13.42 ± 1.17 in the eCG group (19/20) and 13.53 ± 0.19 (14/20) in the control (p = 0.34). The ovulation rate was higher in the eCG group (95%) than in the control (70%). eCG increased the vascularised follicle perimeter on Days 11 (p = 0.018) and 12 (p = 0.03) and enhanced corpus luteum (CL) diameter on Day 16 (p < 0.001). A larger vascularised area was observed on Days 14-16, 20 and 24 (p < 0.05). P4 concentrations were higher in the eCG group on Days 15, 16, 20 and 24 (p < 0.05). Significant correlations were found between CL size, vascularisation and P4 concentration (r = 0.75, p < 0.001). In conclusion, eCG improves ovarian vascularisation, ovulation rates and plasma P4 levels, supporting its use to enhance reproductive performance in buffalo herds.
Keywords: blood flow; Doppler ultrasonography; fixed‐time artificial insemination (FTAI); ovary